Glass, glass elements and filters
By rationally formulating vanadium phosphate, aluminum oxide, copper oxide and rare earth oxide plasma composition in glass, the problem of fluorine volatility in the existing glass during melting is solved, and high-quality near-infrared absorption glass is achieved.
Patent Information
- Application Number
- JP2024554999
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-02-21
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing near-infrared absorbing glass is prone to volatilization of fluorine during the melting process, resulting in unevenness in the glass, making it difficult to meet high-quality requirements.
A specific formula is used, which contains vanadium phosphate, aluminum oxide, copper oxide, rare earth oxide plasma, and the content ratio of each ions is controlled to ensure the absorption performance of the glass in the near infrared range and the transparency in the visible range.
The high internal quality of the glass, excellent visible light transparency and near-infrared absorption performance are achieved, and glass defects caused by fluorine volatility are avoided.
Smart Images

Figure 2025509677000001 
Figure 2025509677000002 
Figure 2025509677000003
Abstract
Description
[Technical field]
[0001] The present invention relates to glass, and more particularly to near infrared absorbing glass. [Background technology]
[0002] In recent years, the spectral sensitivity of semiconductor imaging devices such as CCDs and CMOSs used in digital cameras, camera phones, and VTR cameras has spread from the visible region to the near-infrared region, and by using a filter that absorbs light in the near-infrared region, visibility close to that of humans can be obtained. In general, the wavelength of visible light perceived by the human eye is 400 to 700 nm, and by using a filter that absorbs near-infrared light, an image close to the brightness coefficient of the human eye can be obtained. As the demand for filters for correcting human color sensitivity increases, the requirements for near-infrared absorbing glass used in the manufacture of such filters become higher, and this type of glass is required to have excellent transparency in the visible region and excellent absorption properties in the near-infrared region. Near-infrared absorbing glass in the prior art usually contains a large amount of fluorine (F - For example, Chinese Patent Publication No. 102656125 states that if a large amount of fluorine is contained, the fluorine will volatilize during the glass melting process, which makes it easy for defects such as stripes and internal unevenness to occur in the glass, making it difficult for the inherent quality of the glass to meet requirements. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] China Patent Application Publication No. 102656125 Summary of the Invention [Problem to be solved by the invention]
[0004] As described above, the technical problem to be solved by the present invention is to provide a glass having excellent intrinsic quality, excellent transmission characteristics in the visible range, and excellent absorption characteristics in the near infrared range. [Means for solving the problem]
[0005] The technical solutions adopted in the present invention to solve the technical problems are as follows: (1) Glass containing the following cations in mole percent: P 5+ : 51-72%, Al 3+ : 0~10%, Cu 2+ : 5~25%, Rn + : 5-25%, R 2+ : 1-18%, Ln 3+ : 0 to 8%, and the Rn + Li + , Na + , K + One or more of R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ One or more of Ln 3+ La 3+ , Gd 3+ , Y 3+ One or more of the following: The anion component is O 2- and F - Contains O 2- and F - The total content of O 2- +F - is over 98%.
[0006] (2) The glass according to (1), further comprising the following cation component in mole percent: Zn 2+ : 0 to 10% and / or Si 4+ : 0 to 5%, and / or B 3+ : 0 to 5% and / or Zr 4+ : 0 to 5% and / or Sb 3+ +Sn 4+ +Ce 4+ :0~1%.
[0007] (3) Glass consisting of the following cation components in mole percent: P 5+ : 51-72%, Al 3+ : 0~10%, Cu 2+: 5~25%, Rn + : 5-25%, R 2+ : 1-18%, Ln 3+ : 0-8%, Zn 2+ : 0 to 10%, Si 4+ : 0 to 5%, B 3+ : 0-5%, Zr 4+ : 0-5%, Sb 3+ +Sn 4+ +Ce 4+ : 0 to 1%, and the Rn + Li + , Na + , K + One or more of R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ One or more of Ln 3+ La 3+ , Gd 3+ , Y 3+ The anion component is one or more of O 2- and F - It is.
[0008] (4) The glass according to any one of (1) to (3), containing the following components in mol %: Al 3+ / Ln 3+ is 0.2 or more, preferably Al 3+ / Ln 3+ is 0.2 to 20.0, more preferably Al 3+ / Ln 3+ is 0.5 to 15.0, more preferably Al 3+ / Ln 3+ is 1.0 to 10.0, more preferably Al 3+ / Ln 3+ is 1.5 to 8.0.
[0009] (5) The glass according to any one of (1) to (4), which contains the following components in mol %: Li + / (Mg 2+ +Al 3+ ) is 0.4 to 10.0, preferably Li + / (Mg 2+ +Al 3+) is 0.6 to 7.0, more preferably Li + / (Mg 2+ +Al 3+ ) is 1.0 to 5.0, more preferably Li + / (Mg 2+ +Al 3+ ) is 1.2 to 3.0.
[0010] (6) The glass according to any one of (1) to (5), containing the following components in mol %: Cu 2+ / Al 3+ is 1.0 to 15.0, preferably Cu 2+ / Al 3+ is 2.0 to 10.0, more preferably Cu 2+ / Al 3+ is 3.0 to 8.0, more preferably Cu 2+ / Al 3+ is 4.0 to 7.0.
[0011] (7) The glass according to any one of (1) to (6), which contains the following components in mol %: (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.3 to 6.0, preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.5 to 5.0, more preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.7 to 3.0, more preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.8 to 2.0.
[0012] (8) The glass according to any one of (1) to (7), containing the following components in mol %: Ln 3+ / R 2+ is 0.01 or more, preferably Ln 3+ / R 2+ is 0.01 to 3.0, more preferably Ln 3+ / R2+ is 0.03 to 1.0, more preferably Ln 3+ / R 2+ is 0.05 to 0.8, and more preferably Ln 3+ / R 2+ is 0.07 to 0.5.
[0013] (9) The glass according to any one of (1) to (8), comprising the following components in mol %: Ln 3+ / (Ba 2+ +Al 3+ ) is 0.02 or more, preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.02 to 2.0, more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.05 to 1.0, more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.08 to 0.8, and more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.1 to 0.5.
[0014] (10) A glass according to any one of (1) to (9), comprising the following components in mol %: 5+ / (Al 3+ +Ln 3+ ) is 5.0 to 50.0, preferably P 5+ / (Al 3+ +Ln 3+ ) is 10.0 to 35.0, more preferably P 5+ / (Al 3+ +Ln 3+ ) is 12.0 to 30.0, more preferably P 5+ / (Al 3+ +Ln 3+ ) is 15.0~25.0.
[0015] (11) The glass according to any one of (1) to (10), containing the following components in mol %: Cu 2+ / Ln 3+ is 2.0 or more, preferably Cu 2+ / Ln3+ is 2.0 to 40.0, more preferably Cu 2+ / Ln 3+ is 5.0 to 30.0, more preferably Cu 2+ / Ln 3+ is 8.0 to 20.0, more preferably Cu 2+ / Ln 3+ is 10.0 to 15.0.
[0016] (12) The glass according to any one of (1) to (11), containing the following components in mol %: 5+ / R 2+ is 3.0 to 30.0, preferably P 5+ / R 2+ is 3.5 to 25.0, more preferably P 5+ / R 2+ is 4.0 to 20.0, more preferably P 5+ / R 2+ is 5.0~10.0.
[0017] (13) The glass according to any one of (1) to (12), comprising the following components in mol %: Ln 3+ / F - is 0.01 or more, preferably Ln 3+ / F - is 0.02 to 10.0, more preferably Ln 3+ / F - is 0.05 to 5.0, more preferably Ln 3+ / F - is 0.05 to 2.0, and more preferably Ln 3+ / F - is between 0.1 and 1.0.
[0018] (14) The glass according to any one of (1) to (13), comprising the following component in mol %: - / Cu 2+ is 0.05 to 2.0, preferably F - / Cu 2+ is 0.1 to 1.5, more preferably F - / Cu 2+ is 0.2 to 1.0, more preferably F - / Cu 2+ is 0.3 to 0.8.
[0019] (15) A glass according to any one of (1) to (14), comprising the following components in mol %: 5+ : 56 to 68%, preferably P 5+ : 60 to 65% and / or Al 3+ : 0.5 to 8%, preferably Al 3+ : 1 to 5% and / or Cu 2+ : 6 to 20%, preferably Cu 2+ : 8 to 15%, and / or Rn + : 7 to 20%, preferably Rn + : 10-17%, and / or R 2+ : 3 to 16%, preferably R 2+ : 5 to 14%, and / or Ln 3+ : 0.1 to 6%, preferably Ln 3+ : 0.5 to 4% and / or Zn 2+ : 0 to 5%, preferably Zn 2+ : 0 to 2% and / or Si 4+ : 0 to 2%, preferably Si 4+ : 0 to 1%, and / or B 3+ : 0 to 2%, preferably B 3+ : 0 to 1% and / or Zr 4+ 0 to 2%, preferably Zr 4+ : 0 to 1% and / or Sb 3+ +Sn 4+ +Ce 4+ 0 to 0.5%, preferably Sb 3+ +Sn 4+ +Ce 4+ : 0 to 0.1%, and the Rn + Li + , Na + , K + R is one or more of the following: 2+ is Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ Ln is one or more of the following: 3+ La 3+ , Gd 3+ , Y 3+ It is one or more of the following.
[0020] (16) The glass according to any one of (1) to (15), comprising the following components in mol %: Li + : 5 to 25%, preferably Li + : 8 to 20%, more preferably Li + : 10 to 16%, and / or Na + : 0 to 10%, preferably Na + : 0 to 5%, more preferably Na + : 0 to 2% and / or K + : 0 to 10%, preferably K + : 0 to 5%, more preferably K + : 0 to 2% and / or Mg 2+ : 0 to 15%, preferably Mg 2+ : 0.5 to 10%, more preferably Mg 2+ : 2 to 8% and / or Ca 2+ : 0 to 10%, preferably Ca 2+ : 0 to 5%, more preferably Ca 2+ : 0-2% and / or Sr 2+ : 0 to 10%, preferably Sr 2+ 0 to 5%, more preferably Sr 2+ : 0 to 2% and / or Ba 2+ : 0 to 10%, preferably Ba 2+ : 0.5 to 8%, more preferably Ba 2+ : 1 to 6%, and / or La 3+ : 0 to 5%, preferably La 3+ : 0 to 3%, more preferably La 3+ : 0 to 2% and / or Gd 3+ : 0 to 5%, preferably Gd 3+ : 0 to 3%, more preferably Gd 3+ : 0 to 2%, and / or Y 3+ : 0 to 6%, preferably Y 3+ : 0.1 to 5%, more preferably Y 3+ :0.5~3%.
[0021] (17) The glass according to (1) or (2), further comprising the following anion component in mol %: Cl - +Br - +I -: 0 to 2%, preferably Cl - +Br - +I - : 0 to 1%, more preferably Cl - +Br - +I - :0~0.5%.
[0022] (18) The glass according to any one of (1) to (17), comprising the following components in mol %: 2- : 85 to 99.5%, preferably O 2- : 88 to 99%, more preferably O 2- : 91-98% and / or F - : 0.5 to 15%, preferably F - : 1 to 12%, more preferably F - :2~9%.
[0023] (19) The glass transition temperature T g is 410°C or less, preferably 400°C or less, more preferably 390°C or less, and even more preferably 370 to 390°C, and / or the density ρ is 3.3 g / cm 3 Less than 3.2 g / cm, preferably 3.2 g / cm 3 Less than or equal to 3.1 g / cm 3 More preferably, 3.0 g / cm 3 and / or the thermal expansion coefficient α 20-120℃ is 110 x 10 -7 / K or less, preferably 100×10 -7 / K or less, preferably 95×10 -7 / K or less, and / or hardness H v is 380kgf / mm 2 More than 390kgf / mm 2 More preferably, 400kgf / mm 2 More preferably, 410 kgf / mm 2 Thus, Young's modulus E is 5500×10 7 ~8500×10 7 Pa, preferably 6000 x 10 7 ~8000×10 7 Pa, more preferably 6500×10 7 ~7500×107 The glass according to any one of (1) to (18), wherein Pa.
[0024] (20) When the thickness of the glass is 0.5 mm or less, the corresponding wavelength λ at which the spectral transmittance reaches 50% in the wavelength range of 500 to 700 nm 50 The glass according to any one of (1) to (19), wherein the wavelength is 635 nm or less, preferably from 600 to 630 nm, and more preferably from 610 to 625 nm.
[0025] (21) When the glass thickness is 0.5 mm or less, the transmittance τ at 400 nm 400 is 80.0% or more, preferably 82.0% or more, more preferably 84.0% or more, and / or the transmittance τ at 500 nm 500 is 83.0% or more, preferably 85.0% or more, more preferably 88.0% or more, and / or the transmittance τ at 1100 nm 1100 The glass according to any one of (1) to (20), wherein the content of C is 10.0% or less, preferably 7.0% or less, more preferably 5.0% or less, and further preferably 3.0% or less.
[0026] (22) The glass according to (20) or (21), wherein the thickness of the glass is 0.05 to 0.4 mm, preferably 0.1 to 0.3 mm, and more preferably 0.1 mm or 0.15 mm or 0.2 mm or 0.25 mm.
[0027] (23) A glass element comprising the glass according to any one of (1) to (21).
[0028] (24) A filter comprising the glass according to any one of (1) to (21) or the glass element according to (23).
[0029] (25) An apparatus comprising the glass according to any one of (1) to (21), or the glass element according to (23), or the filter according to (24). Effect of the Invention
[0030] The beneficial effects of the present invention are as follows: Due to the rational component design, the glass obtained by the present invention has excellent intrinsic quality, excellent transmission characteristics in the visible range and excellent absorption characteristics in the near infrared range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The following describes in detail the embodiments of the present invention, but the present invention is not limited to the embodiments described below, and can be modified as appropriate within the scope of the object of the present invention. Furthermore, although some parts are omitted as appropriate, the gist of the present invention is not limited by repeating the description.
[0032] [Glass] The range of each component constituting the glass of the present invention will be described below.Unless otherwise specified in this specification, the content of a cation component is expressed as the molar percentage (mol%) of the cation component relative to the entire cation components, the content of anion component is expressed as the molar percentage (mol%) of the anion component relative to the entire anion components, the ratio between the contents of the cation components is the molar percentage content ratio between the contents of each cation component, the ratio between the contents of the anion components is the molar percentage content ratio between the contents of each anion component, and the ratio between the contents of anion and cation components is the ratio between the molar percentage content of the cation component in the entire cation components and the molar percentage content of the anion component in the entire anion components.
[0033] Specifically, the numerical ranges described herein include upper and lower limits, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions subsumed within the range, but are not limited to the specific values set forth when the range is limited. As used herein, "and / or" is inclusive, e.g., "A and / or B" means A only, B only, or both A and B.
[0034] The ionic valence of each component described below is a representative value used for convenience, and is not distinguished from other ionic valences. The ionic valence of each component in glass may be other than the representative value. For example, P is usually present in glass in a +5 ionic valence state, so in this patent, it is referred to as "P 5+ " is representative, however, other ionic valence states may exist and are also covered by this patent.
[0035] <Cationic components> P 5+ is an essential component for constituting the glass skeleton of the present invention, promotes glass formation, and is advantageous in improving the near-infrared absorption performance of the glass. 5+ If the content is less than 51%, the above effects are insufficient, and the near-infrared absorption function of the glass cannot meet the design requirements. 5+ If the content of P exceeds 72%, the crystallization tendency of the glass increases and the weather resistance decreases. 5+ In some embodiments, the P content is about 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, or 72%. 5+ can be included.
[0036] Al 3+ Al is advantageous in improving the stability of glass, increasing the strength of glass, and improving the weather resistance of glass. However, if its content exceeds 10%, the tendency of glass to crystallize increases and the melting performance of glass deteriorates. Therefore, in the present invention, Al is 3+ The content of Al is 0 to 10%, preferably 0.5 to 8%, and more preferably 1 to 5%. In some embodiments, the content of Al is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10%. 3+ can be included.
[0037] Cu 2+ is a component necessary for the glass of the present invention to obtain near-infrared absorbing performance. If the content of Cu is less than 5%, it is difficult for the near-infrared absorbing performance of the glass to meet the design requirements. 2+ If the content of Cu exceeds 25%, the transmittance of the glass in the visible range decreases, the valence state of Cu in the glass changes, it becomes difficult to obtain the expected light absorption performance, and the devitrification resistance of the glass decreases. 2+ In some embodiments, the Cu content is about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%. 2+ can be included.
[0038] In some embodiments, Cu 2+ Content and Al 3+ Ratio of Cu content to 2+ / Al 3+ By controlling the value of Cu to be within the range of 1.0 to 15.0, the glass has excellent transmittance in the visible range, improves the near-infrared absorption performance of the glass, and can obtain an appropriate Young's modulus. 2+ / Al 3+ is 1.0 to 15.0, more preferably Cu 2+ / Al 3+ is 2.0 to 10.0, more preferably Cu 2+ / Al 3+ is 3.0 to 8.0, and more preferably Cu 2+ / Al 3+ In some embodiments, Cu 2+ / Al 3+The values can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0.
[0039] Ln 3+ (Ln 3+ La 3+ , Gd 3+ , Y 3+ Ln (one or more of these) is advantageous in increasing the visible light transmittance and near infrared absorption performance of the glass and improving the chemical stability and hardness of the glass. However, if its content exceeds 8%, the crystallization resistance of the glass deteriorates. 3+ The content of Ln is 8% or less, preferably 0.1 to 6%, and more preferably 0.5 to 4%. In some embodiments, the content of Ln is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, or 8%. 3+ can be included.
[0040] Y 3+ In glass, La 3+ and Gd 3+ It is more advantageous to obtain the expected spectral characteristics of the present invention than Y 3+ The content of is preferably 0 to 6%, more preferably 0.1 to 5%, and further preferably 0.5 to 3%. 3+ The content of is preferably 0 to 5%, more preferably 0 to 3%, and further preferably 0 to 2%. 3+The content of Y is preferably 0 to 5%, more preferably 0 to 3%, and even more preferably 0 to 2%. In some embodiments, the content of Y is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, or 6%. 3+ In some embodiments, the cellulose may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5% La. 3+ In some embodiments, the Gd may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%. 3+ can be included.
[0041] In some embodiments, Al 3+ Content and Ln 3+ Ratio of Al content to 3+ / Ln 3+ By controlling the value of Al to 0.2 or more, it is advantageous for the glass to have an appropriate Young's modulus and abrasion degree. 3+ / Ln 3+ is 0.2 or more, more preferably Al 3+ / Ln 3+ is 0.2 to 20.0, more preferably Al 3+ / Ln3+ is 0.5 to 15.0. Furthermore, Al 3+ / Ln 3+ By controlling the content of Al in the range of 1.0 to 10.0, it is possible to obtain a high hardness of the glass and at the same time to prevent an increase in the glass transition temperature. 3+ / Ln 3+ is 1.0 to 10.0, and most preferably Al 3+ / Ln 3+ In some embodiments, Al 3+ / Ln 3+ The values are 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4. .0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0.
[0042] In some embodiments, P 5+ / (Al 3+ +Ln 3+ By controlling the content of P in the range of 5.0 to 50.0, the hardness of the glass can be increased and an increase in the glass density can be prevented. 5+ / (Al 3+ +Ln 3+ ) is 5.0 to 50.0, more preferably P 5+ / (Al 3+ +Ln 3+ ) is 10.0 to 35.0. Furthermore, P 5+ / (Al 3+ +Ln 3+ By controlling the value of P within the range of 12.0 to 30.0, the visible light transmittance of the glass can be further increased.5+ / (Al 3+ +Ln 3+ ) is 12.0 to 30.0, and more preferably P 5+ / (Al 3+ +Ln 3+ In some embodiments, P 5+ / (Al 3+ +Ln 3+ ) can have values of 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0.
[0043] In some embodiments, Cu 2+ / Ln 3+ By controlling the value of Cu to 2.0 or more, it is advantageous to improve the near infrared ray absorption performance of the glass. 2+ / Ln 3+ is 2.0 or more, more preferably Cu 2+ / Ln 3+ is 2.0 to 40.0. Furthermore, Cu 2+ / Ln 3+ By controlling the content of Cu in the range of 5.0 to 30.0, it is advantageous to increase the hardness of the glass and to lower the transition temperature. 2+ / Ln 3+ is 5.0 to 30.0, and more preferably Cu 2+ / Ln 3+ is 8.0 to 20.0, and extremely preferably Cu 2+ / Ln 3+ In some embodiments, Cu 2+ / Ln 3+The values of can be 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0.
[0044] Rn + (Rn + Li + , Na + , K + (one or more of) lowers the melting temperature and viscosity of the glass, 2+ The presence of Cu in the ZnO state can be promoted, but Rn + As Rn increases, the chemical stability of the glass deteriorates. + The above performance is achieved by adding Rn + If the content of Rn exceeds 25%, the devitrification resistance of the glass decreases, the moldability of the glass deteriorates, and the thermal expansion coefficient increases. + In some embodiments, the content of Rn is about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, or 25%. + can be included.
[0045] Li + It can reduce the melting temperature and viscosity of glass and improve the visible light transmittance of glass, while contributing to chemical stability. + and K. + In the present invention, it is preferable that the content of Li is 5% or more.+ However, Li + If the content of Li exceeds 25%, the devitrification resistance and forming ability of the glass are deteriorated. + The lower limit of the content of Li is preferably 5%, more preferably 8%, and even more preferably 10%. + The upper limit of the Li content is preferably 25%, more preferably 20%, and even more preferably 16%. In some embodiments, the Li content is about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%. + can be included.
[0046] Na + is a component that improves the meltability of glass. In the present invention, Na + By controlling the content to 10% or less, the chemical stability of the glass can be improved and deterioration of weather resistance and processability can be prevented. + The content is 5% or less, more preferably Na + In some embodiments, the content of Na is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. + can be included.
[0047] K + can increase the transmittance of glass in the visible range, and if its content exceeds 10%, the stability of the glass decreases. +In some embodiments, the content of K is limited to 10% or less, preferably 5% or less, and more preferably 2% or less. In some embodiments, the content of K is limited to about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. + can be included.
[0048] R 2+ (R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ (one or more of) can be used to lower the melting temperature and thermal expansion coefficient of glass and improve the forming stability and strength of glass, but R 2+ When the content of R exceeds 18%, the devitrification resistance of the glass decreases. 2+ In some embodiments, the content of R is about 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, or 18%. 2+ can be included.
[0049] In some embodiments, Ln 3+ / R 2+ By controlling Ln to 0.01 or more, the crystallization resistance of the glass can be optimized, which is advantageous in lowering the thermal expansion coefficient of the glass. Therefore, it is preferable to 3+ / R 2+ is 0.01 or more, more preferably Ln 3+ / R 2+ is 0.01 to 3.0. Furthermore, Ln 3+ / R 2+Controlling Ln within the range of 0.03 to 1.0 is also advantageous in improving the near-infrared absorption performance of the glass. Therefore, it is more preferable that Ln 3+ / R 2+ is 0.03 to 1.0, and even more preferably Ln 3+ / R 2+ is 0.05 to 0.8, and extremely preferably Ln 3+ / R 2+ In some embodiments, Ln 3+ / R 2+ The values of are 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3 , 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0.
[0050] In some embodiments, P 5+ / R 2+ By controlling P within the range of 3.0 to 30.0, it is advantageous to increase the chemical stability of the glass and to reduce the density and thermal expansion coefficient of the glass. 5+ / R 2+ is 3.0 to 30.0, more preferably P 5+ / R 2+ is 3.5 to 25.0, and more preferably P 5+ / R 2+ is 4.0 to 20.0, and more preferably P 5+ / R 2+ In some embodiments, P 5+ / R 2+The values are 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, It can be 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.
[0051] Mg 2+ can lower the melting temperature of glass and improve the processing performance of glass, but if its content exceeds 15%, the crystallization resistance of glass decreases. 2+ The content is 15% or less, preferably Mg 2+ The content is preferably 0.5 to 10%, more preferably Mg 2+ In some embodiments, the content of Mg is about 0%, 0% or more, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% Mg 2+ can be included.
[0052] In some embodiments, Li + / (Mg 2+ +Al 3+ By controlling the value of Li within the range of 0.4 to 10.0, the glass can have excellent transmittance in the visible range, the near-infrared absorption of the glass can be increased, and an increase in the glass density and the thermal expansion coefficient can be prevented. Therefore, it is preferable to use Li + / (Mg 2+ +Al 3+ ) is 0.4 to 10.0, more preferably Li + / (Mg 2+ +Al 3+) is 0.6 to 7.0, more preferably Li + / (Mg 2+ +Al 3+ ) is 1.0 to 5.0, and even more preferably Li + / (Mg 2+ +Al 3+ ) is 1.2 to 3.0. In some embodiments, Li + / (Mg 2+ +Al 3+ ) values are 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3. It can be 7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.3, 5.5, 5.7, 6.0, 6.3, 6.5, 6.7, 7.0, 7.3, 7.5, 7.7, 8.0, 8.3, 8.5, 8.7, 9.0, 9.3, 9.5, 9.7, 10.0.
[0053] In some embodiments, (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ By controlling the value of (Cu) within the range of 0.3 to 6.0, the glass can have an appropriate Young's modulus and at the same time, the hardness of the glass can be increased. 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.3 to 6.0, more preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.5 to 5.0, more preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) is 0.7 to 3.0, and even more preferably (Cu 2+ +Mg 2+ ) / (Li + +Al 3+) is 0.8 to 2.0. In some embodiments, (Cu 2+ +Mg 2+ ) / (Li + +Al 3+ ) can have values of 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0.
[0054] Less than 10% Ca 2+ By adding Ca, it is possible to reduce the high temperature viscosity of the glass and at the same time prevent the deterioration of the crystallization resistance. 2+ In some embodiments, the content of Ca is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. 2+ can be included.
[0055] Sr less than 10% 2+ The addition of Sr can prevent the deterioration of the chemical stability and crystallization resistance of the glass. 2+ In some embodiments, the content of Sr is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. 2+ can be included.
[0056] Ba 2+Ba can increase the transmittance of glass in the visible range and improve the forming stability and strength of glass, but if its content exceeds 10%, the density of glass increases. In some embodiments of the present invention, Ba 2+ By controlling the content of Ba to 0.5% or more, the chemical stability of the glass can be improved and the thermal expansion coefficient of the glass can be reduced. 2+ The content of Ba is 10% or less, preferably 0.5 to 8%, and more preferably 1 to 6%. In some embodiments, the content of Ba is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10%. 2+ can be included.
[0057] In some embodiments, Ln 3+ / (Ba 2+ +Al 3+ By controlling Ln to 0.02 or more, it is advantageous to lower the thermal expansion coefficient of the glass and at the same time prevent the transition temperature from increasing. Therefore, it is preferable to 3+ / (Ba 2+ +Al 3+ ) is 0.02 or more, and more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.02 to 2.0, more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.05 to 1.0. Furthermore, Ln 3+ / (Ba 2+ +Al 3+ ) in the range of 0.08 to 0.8 is advantageous in optimizing the hardness of the glass. Therefore, it is even more preferable to 3+ / (Ba 2+ +Al 3+ ) is 0.08 to 0.8, and extremely preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.1 to 0.5.
[0058] B3+ can lower the melting temperature of glass, but if its content exceeds 5%, the near infrared absorption properties are reduced. 3+ The content of is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably B 3+ In some embodiments, the B content is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. 3+ can be included.
[0059] S 4+ Although Si can promote glass formation and increase the chemical stability of glass, if its content exceeds 5%, the melting property of glass is deteriorated, unmelted impurities are easily formed in the glass, and the near-infrared absorption property of the glass is easily deteriorated. Therefore, Si 4+ The content of is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably Si 4+ In some embodiments, the concentration is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Si. 4+ can be included.
[0060] Zinc 2+ can lower the glass transition temperature and increase the thermal stability of glass, but if its content exceeds 10%, the devitrification resistance of glass decreases. 2+ The content of Zn is limited to 10% or less, preferably 5% or less, and more preferably 2% or less. In some embodiments, it is further preferred that Zn 2+ In some embodiments, the compound is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Zn. 2+ can be included.
[0061] Zr 4+Zr can improve the chemical stability of glass, but if its content exceeds 5%, the melting performance of glass will be significantly reduced and the crystallization resistance will be reduced. 4+ The content of is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably Zr 4+ In some embodiments, the Zr content is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. 4+ can be included.
[0062] Sb 3+ , Sn 4+ , Ce 4+ One or more of the components can be used as fining agents to improve the fining effect of glass and increase the bubble level of glass. 3+ , Sn 4+ , Ce 4+ The single or total content of Sb is 0 to 1%, preferably 0 to 0.5%, and more preferably 0 to 0.1%. In some embodiments, the content of Sb is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. 3+ and / or Sn 4+ and / or Ce 4+ can be included.
[0063] <Anion components> The anion component of the glass of the present invention is mainly O 2- and F - In order to provide the glass of the present invention with excellent stability and resistance to devitrification, 2- and F - The total content of O 2- +F - In some embodiments, the O 2- +F -can be 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 100%.
[0064] O 2- is an important anion component in the glass of the present invention. In addition to stabilizing the network structure and forming a stable glass, the Cu ions in the glass also act as Cu 2+ and further ensures the light absorption properties of the glass in the near infrared region. 2- If the content of Cu is too low, it is difficult to form a stable glass. 2+ Cu + It is difficult to achieve a light absorption effect in the near infrared range, however, 2- If the O content is too high, the melting temperature of the glass becomes high and the light transmittance in the visible range decreases significantly. 2- In some embodiments, the O content is limited to about 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, or 99.5%. 2- can be included.
[0065] F - F can lower the melting temperature of glass, increase the transmittance of glass in the visible range, and reduce the viscosity of glass. It is advantageous to increase the crystallization resistance of glass by adding an appropriate amount. - If the content of F exceeds 15%, the stability of the glass is reduced, it is easy to volatilize during melting of the glass, it pollutes the environment, and it is easy to cause stripes on the glass. -The content of F is limited to 0.5-15%, preferably 1-12%, and more preferably 2-9%. In some embodiments, the content of F is about 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%. - can be included.
[0066] In some embodiments, Ln 3+ / F - By controlling Ln to 0.01 or more, the near infrared absorbing performance of the glass can be improved and the glass transition temperature can be prevented from increasing. Therefore, it is preferable to control Ln 3+ / F - is 0.01 or more, more preferably Ln 3+ / F - is 0.02 to 10.0, more preferably Ln 3+ / F - is 0.05 to 5.0. Furthermore, Ln 3+ / F - By controlling Ln within the range of 0.05 to 2.0, the glass can obtain an appropriate Young's modulus. Therefore, it is even more preferable to 3+ / F - is 0.05 to 2.0, and extremely preferably Ln 3+ / F - In some embodiments, Ln 3+ / F -The values of are 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, It can be 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.
[0067] In some embodiments, F - / Cu 2+ By controlling F within the range of 0.05 to 2.0, the glass can obtain an appropriate Young's modulus and a low thermal expansion coefficient. - / Cu 2+ is 0.05 to 2.0, more preferably F - / Cu 2+ is 0.1 to 1.5, and more preferably F - / Cu 2+ is 0.2 to 1.0, and more preferably F - / Cu 2+ In some embodiments, F - / Cu 2+ The values of can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0.
[0068] Cl - , Br - , I - One or more of the components can be used as a fining agent to improve the fining effect of glass and increase the bubble level of glass. - , Br - , I - The content of each of these alone or in total is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.5%. In some embodiments, the content of each of these alone or in total is about 0%, 0% or more, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2% Cl. - and / or Br - And / or I - can be included.
[0069] <Ingredients not included> Components such as V, Cr, Mn, Fe, Co, Ni, Ag and Mo, even when present alone or in combination in small amounts, interfere with the spectral transmittance of the glass and are detrimental to the formation of the glass of the present invention, and therefore are preferably free of the above components.
[0070] In recent years, there has been a trend to refrain from using As, Pb, Th, Cd, Tl, Os, Be and Se components as harmful chemical substances, and it is necessary to take measures to protect the environment not only in the glass manufacturing process but also in the processing process and post-production treatment. Therefore, when the impact on the environment is important, it is preferable that they are not included except for unavoidable contamination. This makes the glass actually free of substances that pollute the environment. Therefore, the glass of the present invention can be manufactured, processed and disposed of without taking special environmental measures.
[0071] The terms "free" and "0%" used herein mean that the component was not intentionally added to the raw materials of the present invention. However, impurities or components that are not intentionally added to the raw materials and / or equipment used to manufacture the glass may be present in small or trace amounts in the final glass, and are also covered by the present invention.
[0072] [Manufacturing method] The method for producing the glass of the present invention is as follows: The glass of the present invention is produced by conventional raw materials and conventional processes, such as carbonates, nitrates, sulfates, phosphates, metaphosphates, sulfates, hydroxides, oxides, and fluorides, and after mixing by a conventional method, the prepared refractory material is put into a melting furnace at 700 to 1000 ° C. and melted. Then, it is clarified, stirred, and homogenized to obtain a homogeneous molten glass without bubbles or unmelted materials, and this molten glass is cast into a mold and annealed. Those skilled in the art can appropriately select the raw materials, manufacturing methods, and process parameters according to actual needs.
[0073] The glasses of the present invention can also be formed by known methods. In some embodiments, the glasses described herein can be made into formed bodies through various processes, including but not limited to sheets, including but not limited to drawdown, float, roll press, and other sheet forming processes known in the art. Alternatively, the glasses are made by float or roll press processes known in the art.
[0074] The glass of the present invention can be used to produce a sheet-like glass molded product by methods such as grinding and polishing, but the method for producing the glass molded product is not limited to these methods.
[0075] The glasses and glass bodies according to the present invention can have any reasonable and useful thickness.
[0076] The characteristics of the glass of the present invention will now be described.
[0077] <Transition temperature> Glass transition temperature (T g ) is tested in accordance with the method specified in GB / T7962.16-2010.
[0078] In some embodiments, the transition temperature (T g ) is 410°C or less, preferably 400°C or less, more preferably 390°C or less, and further preferably 370 to 390°C.
[0079] <density> The density (ρ) of the glass is tested according to the method specified in GB / T7962.20-2010.
[0080] In some embodiments, the density (ρ) of the glasses of the present invention is 3.3 g / cm 3 Less than 3.2 g / cm, preferably 3.2 g / cm 3 Less than or equal to 3.1 g / cm 3 More preferably, 3.0 g / cm 3 The following is the result.
[0081] <Thermal expansion coefficient> Thermal expansion coefficient of glass (α 20-120°C ) is tested in accordance with the method specified in GB / T7962.16-2010.
[0082] In some embodiments, the thermal expansion coefficient (α 20-120℃ ) is 110 x 10 -7 / K or less, preferably 100×10 -7 / K or less, preferably 95×10 -7 / K or less.
[0083] <Hardness> Glass hardness (H v The surface area (mm2) of the specimen is calculated by the load (N) applied to the test surface using a diamond pyramid indenter with an angle of 136° between the opposing faces to press a pyramid-shaped indentation into the test surface, and the surface area (mm2) is calculated by the length of the indentation. 2The test is performed with a test load of 100 (N) and a holding time of 15 (seconds).
[0084] In some embodiments, the hardness (H v ) is 380kgf / mm 2 More than 390kgf / mm 2 More preferably, 400kgf / mm 2 More preferably, 410 kgf / mm 2 That's all.
[0085] <Young's modulus> The Young's modulus (E) of glass is calculated by measuring the longitudinal wave velocity and the shear wave velocity using ultrasound and using the following formula:
number
[0086] In some embodiments, the lower limit of the Young's modulus (E) of the glass of the present invention is 5500×10 7 / Pa, preferably with a lower limit of 6000×10 7 / Pa, and more preferably the lower limit is 6500×10 7 / Pa, the upper limit of Young's modulus (E) is 8500×10 7 / Pa, preferably with an upper limit of 8000×10 7 / Pa, and more preferably, the upper limit is 7500×10 7 / Pa.
[0087] <Spectral transmittance> The spectral transmittance of the glass of the present invention refers to a value obtained by the following method using a spectrophotometer: assuming that a glass sample has two parallel, optically polished planes, and that light is incident perpendicularly on one parallel plane and exits from the other parallel plane, the value obtained by dividing the intensity of this exiting light by the intensity of the incident light is the transmittance, which is also called the external transmittance.
[0088] In some embodiments, when the glass thickness is 0.5 mm or less, the spectral transmittance has the following characteristics:
[0089] Spectral transmittance at 400 nm wavelength (τ 400 ) is 80.0% or more, preferably 82.0% or more, and more preferably 84.0% or more.
[0090] In some embodiments, τ 400are 80.0%, 80.1%, 80.2%, 80.3%, 80.4%, 80.5%, 80.6%, 80.7%, 80.8%, 80.9%, 81.0%, 81.1%, 81.2%, 81.3%, 81.4%, 81.5%, 81.6%, 81.7%, 81.8%, 81.9%, 82.0%, 82.1%, 82.2%, 82.3%, 82.4%, 82.5%, 82.6%, 82.7%, 82.8%, 82.9%, 83.0%, 83.1%, 83.2%, 83.3%, 83.4%, 83.5%, 83.6%, 83.7%, 83.8%, 83.9%, 84.0%, 84.1%, 84.2%, 84.3%, 84.4%, 84.5%, 84.6%, 84.7%, 84.8%, 84.9%, 85.0%, 85.1%, 85.2%, 85.3%, 85.4%, 85.5%, 85.6%, 85.7%, 85.8%, 85.9%, 86.0%, 86.1%, 86.2%, 86.3%, 86.4%, 86.5%, 86.6%, 86.7%, 86.8%, 86.9%, 87.0 ... 2.4%, 82.5%, 82.6%, 82.7%, 82.8%, 82.9%, 83.0%, 83.1%, 83.2%, 83.3%, 83.4%, 83.5%, 83.6%, 83.7%, 83.8%, 83.9%, 84.0%, 84.1%, 84.2%, 84.3%, 84.4%, 84.5%, 84.6%, 84.7%, 84.8 %,84.9%,85.0%,85.1%,85.2%,85.3%,85.4%,85.5%,85.6%,85.7%,85.8%,85.9%,86.0%,86.1%,86.2%,86.3%,86.4%,86.5%,86.6%,86.7%,86.8%,86.9%,87.0%,87.1%,87.2%,87.3%,87.4%,87.5%,87.6%,87.7%,87.8%,87 ...5%,87.6%,87.7%,87.8%,87.9%,87.0%,87.1%,87.2%,87.3%,87.4%,87.5%,87.5%,87.6%,87.7%,87.8 It could be 7.3%, 87.4%, 87.5%, 87.6%, 87.7%, 87.8%, 87.9%, 88.0%, 88.1%, 88.2%, 88.3%, 88.4%, 88.5%, 88.6%, 88.7%, 88.8%, 88.9%, 89.0%, 89.5%, 90.0%, 90.5%, 91.0%, 91.5%, 92.0%.
[0091] Spectral transmittance at 500 nm wavelength (τ 500 ) is 83.0% or more, preferably 85.0% or more, and more preferably 88.0% or more.
[0092] In some embodiments, τ 500are 83.0%, 83.1%, 83.2%, 83.3%, 83.4%, 83.5%, 83.6%, 83.7%, 83.8%, 83.9%, 84.0%, 84.1%, 84.2%, 84.3%, 84.4%, 84.5%, 84.6%, 84.7%, 84.8%, 84.9%, 85.0%, 85.1%, 85.2%, 85.3%, 85.4%, 85.5%, 85.6%, 85.7%, 85.8%, 85.9%, 86.0%, 86.1%, 86.2%, 86.3%, 86.4%, 86.5%, 86.6%, 86.7%, 86.8%, 86.9%, 87.0%, 87.1%, 87.2%, 87.3%, 87.4%, 87.5%, 87.6%, 87.7%, 87.8%, 87.9%, 88.0%, 88.1%, 88.2%, 87.3%, 87.4%, 87.5%, 87.6%, 87.7%, 87.8%, 87.9%, 88.1%, 87 ... 5.4%, 85.5%, 85.6%, 85.7%, 85.8%, 85.9%, 86.0%, 86.1%, 86.2%, 86.3%, 86.4%, 86.5%, 86.6%, 86.7%, 86.8%, 86.9%, 87.0%, 87.1%, 87.2%, 87.3%, 87.4%, 87.5%, 87.6%, 87.7%, 87.8 %,87.9%,88.0%,88.1%,88.2%,88.3%,88.4%,88.5%,88.6%,88.7%,88.8%,88.9%,89.0%,89.1%,89.2%,89.3%,89.4%,89.5%,89.6%,89.7%,89.8%,89.9%,90.0%,90.1%,90.2%,90.3%,90.4%,90.5%,90.6%,90.7%,90.8%,90 ... It can be 0.3%, 90.4%, 90.5%, 90.6%, 90.7%, 90.8%, 90.9%, 91.0%, 91.1%, 91.2%, 91.3%, 91.4%, 91.5%, 91.6%, 91.7%, 91.8%, 91.9%, 92.0%, 92.5%, 93.0%, 93.5%, 94.0%, 94.5%, 95.0%.
[0093] Spectral transmittance at 1100 nm wavelength (τ 1100 ) is 10.0% or less, preferably 7.0% or less, more preferably 5.0% or less, and further preferably 3.0% or less.
[0094] In some embodiments, τ 1100 can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%.
[0095] In some embodiments, when the thickness of the glass is 0.5 mm or less, the corresponding wavelength (λ ) at which the spectral transmittance reaches 50% in the wavelength range of 500 to 700 nm is 50 ) is 635 nm or less, preferably 600 to 630 nm, and more preferably 610 to 625 nm.
[0096] In some embodiments, λ 50 can be 600nm, 601nm, 602nm, 603nm, 604nm, 605nm, 606nm, 607nm, 608nm, 609nm, 610nm, 611nm, 612nm, 613nm, 614nm, 615nm, 616nm, 617nm, 618nm, 619nm, 620nm, 621nm, 622nm, 623nm, 624nm, 625nm, 626nm, 627nm, 628nm, 629nm, 630nm, 631nm, 632nm, 633nm, 634nm, 635nm.
[0097] In the above-mentioned spectral transmittance test, the thickness of the glass is preferably 0.05 to 0.4 mm, more preferably 0.1 to 0.3 mm, and further preferably 0.1 mm, 0.15 mm, 0.2 mm, or 0.25 mm.
[0098] [Glass element] The glass element according to the present invention includes the above-mentioned glass, and examples of the glass element include a thin glass element or lens used in a near-infrared absorbing filter, and is suitable for color correction applications of solid-state imaging devices, and has various excellent performances of the above-mentioned glass. The thickness of the glass element (the distance between the incident surface and the exit surface of transmitted light) is determined by the transmission characteristics of the element, and is preferably 0.05 to 0.4 mm, more preferably 0.1 to 0.3 mm, and further preferably 0.1 mm, 0.15 mm, 0.2 mm, or 0.25 mm, and the wavelength (λ) corresponding to the spectral transmittance at which the transmittance reaches 50% within the wavelength range of 500 to 700 nm is 0.05 to 0.4 mm, more preferably 0.1 to 0.3 mm, and further preferably 0.1 mm, 0.15 mm, 0.2 mm, or 0.25 mm. 50) is 635 nm or less, preferably 600 to 630 nm, and more preferably 610 to 625 nm. In order to obtain such a glass element, the components of the glass are adjusted and processed into an element having a thickness with the above-mentioned spectral characteristics.
[0099] [Filter] The filter according to the present invention is a near-infrared filter, and comprises a near-infrared absorbing element made of near-infrared absorbing glass having optically polished surfaces on both sides and comprising the glass or glass element, and this element imparts a color correction function to the filter while also providing the various excellent performance characteristics of the glass.
[0100] [Equipment] The glass, glass element, or filter of the present invention can be used to manufacture devices such as mobile communication devices such as mobile phones, smart wearable devices, photographing devices, imaging devices, display devices, and monitoring devices by known methods.
[0101] Working Example <Glass Examples> In order to further clearly illustrate the technical solutions of the present invention, the following non-limiting examples are provided. In the present examples, the above-mentioned glass manufacturing method was employed to obtain glasses containing the components shown in Tables 1 to 3. In addition, the properties of each glass were measured by the test methods described in the present invention, and the results are shown in Tables 1 to 3.
[0102] [Table 1]
[0103] [Table 2]
[0104] [Table 3]
[0105] [Table 4]
[0106] [Table 5]
[0107] [Table 6]
[0108] The glasses produced in the examples shown in Tables 1 to 3 above were processed into glass sheets having a thickness of 0.2 mm, and the spectral transmittance of each example glass was measured according to the test method described above. The results are shown in Tables 4 to 6 below.
[0109] [Table 7]
[0110] [Table 8]
[0111] [Table 9]
[0112] <Glass element examples> The glasses of Examples 1 to 24 above can be processed into glass elements by methods known in the art, such as thin glass elements and lenses used in near-infrared absorbing filters, which are suitable for color correction applications in solid-state imaging devices and have the various excellent performance properties of the above glasses.
[0113] <Filter Example> The glasses and / or glass elements of Examples 1 to 24# above are made into filters by methods known in the art, and the filters of the present invention have a color correction function and also have the various excellent properties of the above glasses.
[0114] <Equipment Examples> The glasses and / or glass elements and / or filters of the present invention can be used to manufacture devices such as mobile communication devices such as mobile phones, smart wearable devices, photographic devices, imaging devices, display devices and monitoring devices by known methods, and can also be used in imaging devices, sensors, microscopes, medical technology, digital projection, optical communication technology / information transmission or imaging devices and devices in the automotive field.
Claims
1. Glass containing the following cation components in mole percent: 5+ :51-72%, Al 3+ : 0 to 10%, Cu 2+ : 5 to 25%, Rn + : 5-25%, R 2+ : 1 to 18%, Ln 3+ : 0 to 8%, and the Rn + Li + , Na + , K + R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Ln 3+ La 3+ , Gd 3+ , Y 3+ One or more of the following: The anion component is O 2- and F. - Contains O 2- and F. - The total content of O 2- +F - is over 98%.
2. The glass of claim 1 further comprising the following cationic components in mole percent: Zn 2+ : 0 to 10%, and / or Si 4+ : 0 to 5%, and / or B 3+ : 0 to 5%, and / or Zr 4+ : 0 to 5%, and / or Sb 3+ + Sn 4+ +Ce 4+ : 0 to 1%.
3. Glass consisting of the following cation components in mole percent: 5+ :51-72%, Al 3+ : 0 to 10%, Cu 2+ : 5 to 25%, Rn + : 5-25%, R 2+ : 1 to 18%, Ln 3+ : 0 to 8%, Zn 2+ : 0 to 10%, Si 4+ : 0-5%, B 3+ : 0 to 5%, Zr 4+ : 0 to 5%, Sb 3+ + Sn 4+ +Ce 4+ : 0 to 1%, and the Rn + Li + , Na + , K + R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Ln 3+ La 3+ , Gd 3+ , Y 3+ The anion component is one or more of O 2- and F. - It is.
4. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Al 3+ / Ln 3+ is 0.2 or more, preferably Al 3+ / Ln 3+ is 0.2 to 20.0, more preferably Al 3+ / Ln 3+ is 0.5 to 15.0, more preferably Al 3+ / Ln 3+ is 1.0 to 10.0, and even more preferably Al 3+ / Ln 3+ is 1.5 to 8.
0.
5. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Li + / (Mg 2+ +Al 3+ ) is 0.4 to 10.0, preferably Li + / (Mg 2+ +Al 3+ ) is 0.6 to 7.0, more preferably Li + / (Mg 2+ +Al 3+ ) is 1.0 to 5.0, more preferably Li + / (Mg 2+ +Al 3+ ) is 1.2 to 3.
0.
6. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Cu 2+ / Al 3+ is 1.0 to 15.0, preferably Cu 2+ / Al 3+ is 2.0 to 10.0, more preferably Cu 2+ / Al 3+ is 3.0 to 8.0, more preferably Cu 2+ / Al 3+ is 4.0 to 7.
0.
7. The glass according to any one of claims 1 to 3, comprising the following components in mol%: (Cu 2+ + Mg 2+ ) / (Li + +Al 3+ ) is 0.3 to 6.0, preferably (Cu 2+ + Mg 2+ ) / (Li + +Al 3+ ) is 0.5 to 5.0, more preferably (Cu 2+ + Mg 2+ ) / (Li + +Al 3+ ) is 0.7 to 3.0, more preferably (Cu 2+ + Mg 2+ ) / (Li + +Al 3+ ) is 0.8 to 2.
0.
8. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Ln 3+ / R 2+ is 0.01 or more, preferably Ln 3+ / R 2+ is 0.01 to 3.0, more preferably Ln 3+ / R 2+ is 0.03 to 1.0, more preferably Ln 3+ / R 2+ is 0.05 to 0.8, and even more preferably Ln 3+ / R 2+ is 0.07 to 0.
5.
9. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Ln 3+ / (Ba 2+ +Al 3+ ) is 0.02 or more, preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.02 to 2.0, more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.05 to 1.0, more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.08 to 0.8, and even more preferably Ln 3+ / (Ba 2+ +Al 3+ ) is 0.1 to 0.
5.
10. The glass according to any one of claims 1 to 3, comprising the following components in mol %: P 5+ / (Al 3+ + Ln 3+ ) is 5.0 to 50.0, preferably P 5+ / (Al 3+ + Ln 3+ ) is 10.0 to 35.0, more preferably P 5+ / (Al 3+ + Ln 3+ ) is 12.0 to 30.0, more preferably P 5+ / (Al 3+ + Ln 3+ ) is 15.0 to 25.
0.
11. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Cu 2+ / Ln 3+ is 2.0 or more, preferably Cu 2+ / Ln 3+ is 2.0 to 40.0, more preferably Cu 2+ / Ln 3+ is 5.0 to 30.0, more preferably Cu 2+ / Ln 3+ is 8.0 to 20.0, and even more preferably Cu 2+ / Ln 3+ is 10.0 to 15.
0.
12. The glass according to any one of claims 1 to 3, comprising the following components in mol %: P 5+ / R 2+ is 3.0 to 30.0, preferably P 5+ / R 2+ is 3.5 to 25.0, more preferably P 5+ / R 2+ is 4.0 to 20.0, more preferably P 5+ / R 2+ is 5.0 to 10.
0.
13. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Ln 3+ / F - is 0.01 or more, preferably Ln 3+ / F - is 0.02 to 10.0, more preferably Ln 3+ / F - is 0.05 to 5.0, more preferably Ln 3+ / F - is 0.05 to 2.0, and even more preferably Ln 3+ / F - is 0.1 to 1.
0.
14. The glass according to any one of claims 1 to 3, comprising the following components in mol%: F - / Cu 2+ is 0.05 to 2.0, preferably F - / Cu 2+ is 0.1 to 1.5, more preferably F - / Cu 2+ is 0.2 to 1.0, more preferably F - / Cu 2+ is 0.3 to 0.
8.
15. The glass according to any one of claims 1 to 3, comprising the following components in mol %: P 5+ : 56 to 68%, preferably P 5+ : 60 to 65%, and / or Al 3+ : 0.5 to 8%, preferably Al 3+ : 1 to 5%, and / or Cu 2+ : 6 to 20%, preferably Cu 2+ : 8 to 15%, and / or Rn + : 7 to 20%, preferably Rn + : 10 to 17%, and / or R 2+ : 3 to 16%, preferably R 2+ : 5 to 14%, and / or Ln 3+ : 0.1 to 6%, preferably Ln 3+ : 0.5 to 4%, and / or Zn 2+ : 0 to 5%, preferably Zn 2+ : 0 to 2%, and / or Si 4+ : 0 to 2%, preferably Si 4+ : 0 to 1%, and / or B 3+ : 0 to 2%, preferably B 3+ : 0 to 1%, and / or Zr 4+ 0 to 2%, preferably Zr 4+ : 0 to 1%, and / or Sb 3+ + Sn 4+ +Ce 4+ : 0 to 0.5%, preferably Sb 3+ + Sn 4+ +Ce 4+ : 0 to 0.1%, and the Rn + Li + , Na + , K + One or more of the following: R 2+ is Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Ln is one or more of the following: 3+ La 3+ , Gd 3+ , Y 3+ It is one or more of the following.
16. The glass according to any one of claims 1 to 3, comprising the following components in mol%: Li + : 5 to 25%, preferably Li + : 8 to 20%, more preferably Li + : 10 to 16%, and / or Na + : 0 to 10%, preferably Na + : 0 to 5%, more preferably Na + : 0 to 2%, and / or K + : 0 to 10%, preferably K + : 0 to 5%, more preferably K + : 0 to 2%, and / or Mg 2+ : 0 to 15%, preferably Mg 2+ : 0.5 to 10%, more preferably Mg 2+ : 2 to 8%, and / or Ca 2+ : 0 to 10%, preferably Ca 2+ : 0 to 5%, more preferably Ca 2+ : 0 to 2%, and / or Sr 2+ : 0 to 10%, preferably Sr 2+ : 0 to 5%, more preferably Sr 2+ : 0 to 2%, and / or Ba 2+ : 0 to 10%, preferably Ba 2+ : 0.5 to 8%, more preferably Ba 2+ : 1 to 6%, and / or La 3+ : 0 to 5%, preferably La 3+ : 0 to 3%, more preferably La 3+ : 0 to 2%, and / or Gd 3+ : 0 to 5%, preferably Gd 3+ : 0 to 3%, more preferably Gd 3+ : 0 to 2%, and / or Y 3+ : 0 to 6%, preferably Y 3+ : 0.1 to 5%, more preferably Y 3+ : 0.5-3%.
17. The glass according to claim 1 or 2, further comprising the following anionic components in mol %: Cl - +Br - +I - : 0 to 2%, preferably Cl - +Br - +I - : 0 to 1%, more preferably Cl - +Br - +I - : 0 to 0.5%.
18. The glass according to any one of claims 1 to 3, comprising the following components in mol %: O 2- : 85 to 99.5%, preferably O 2- : 88 to 99%, more preferably O 2- : 91 to 98%, and / or F - : 0.5 to 15%, preferably F - : 1 to 12%, more preferably F - : 2-9%.
19. The glass transition temperature T g is 410° C. or less, preferably 400° C. or less, more preferably 390° C. or less, and even more preferably 370 to 390° C.; and / or density ρ is 3.3 g / cm 3 Less than 3.2 g / cm 3 Less than 3.1 g / cm, more preferably 3.1 g / cm 3 More preferably 3.0 g / cm 3 and / or the thermal expansion coefficient α 20-120℃ is 110 x 10 -7 / K or less, preferably 100×10 -7 / K or less, more preferably 95×10 -7 / K or less, and / or hardness H v is 380 kgf / mm 2 More than 390 kgf / mm 2 More preferably, 400 kgf / mm 2 More preferably, 410 kgf / mm 2 Thus, Young's modulus E is 5500×10 7 ~8500 x 10 7 Pa, preferably 6000×10 7 ~8000 x 10 7 Pa, more preferably 6500×10 7 ~7500 x 10 7 The glass according to any one of claims 1 to 3, wherein
20. When the thickness of the glass is 0.5 mm or less, the corresponding wavelength λ when the spectral transmittance reaches 50% in the wavelength range of 500 to 700 nm 50 The glass according to any one of claims 1 to 3, wherein the optical transmittance is 635 nm or less, preferably between 600 and 630 nm, more preferably between 610 and 625 nm.
21. When the glass thickness is 0.5 mm or less, the transmittance τ at 400 nm 400 is 80.0% or more, preferably 82.0% or more, more preferably 84.0% or more, and / or the transmittance τ at 500 nm 500 is 83.0% or more, preferably 85.0% or more, more preferably 88.0% or more, and / or the transmittance τ at 1100 nm 1100 The glass according to any one of claims 1 to 3, wherein the content of C is 10.0% or less, preferably 7.0% or less, more preferably 5.0% or less, and further preferably 3.0% or less.
22. A glass according to claim 20 or 21, wherein the thickness of the glass is from 0.05 to 0.4 mm, preferably from 0.1 to 0.3 mm, more preferably 0.1 mm or 0.15 mm or 0.2 mm or 0.25 mm.
23. A glass element comprising the glass according to any one of claims 1 to 21.
24. A filter comprising a glass according to any one of claims 1 to 21 or a glass element according to claim 23.
25. An installation comprising a glass according to any one of claims 1 to 21, or a glass element according to claim 23, or a filter according to claim 24.
Citation Information
Patent Citations
Filter glass for cutting near-infrared rays
JP1988025245A
Near infrared-ray cutting filter glass
JP1994234546A
Infrared absorption glass
JP2009263190A
Filter glass for cutting near-infrared ray
JP2010052987A
Filter glass
JP2023133230A